2021
DOI: 10.3390/en14196074
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Increase of Energy Systems in Oil and Gas Industry by Evaluation of Electric Drive Lifecycle

Abstract: The efficiency issue of energy systems in the oil and gas industry is a crucial factor nowadays. Energy share in the production costs of oil and gas can reach 50%. Among the most important energy equipment are the electric drives of the pumps, compressors, auxiliary units, etc. The paper considered the lifecycle of the electric drives used at oil and gas fields and evaluated their efficiency parameters during periods of operational wear or malfunctioning. At the same time, the lifecycle of the energy equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…with the basis value of the impedance of the ideal centralized power system. The Zs changed in a range of 0.1 to 10 to correspond to the transfer of power supply mode from the centralized to the distributed and vice versa [17], [36]. Using the previous research results [14], the most effective control method of the shunt active filter was identified under changes in the parameters of the power source and the connected load.…”
Section: Simulation Modelmentioning
confidence: 99%
“…with the basis value of the impedance of the ideal centralized power system. The Zs changed in a range of 0.1 to 10 to correspond to the transfer of power supply mode from the centralized to the distributed and vice versa [17], [36]. Using the previous research results [14], the most effective control method of the shunt active filter was identified under changes in the parameters of the power source and the connected load.…”
Section: Simulation Modelmentioning
confidence: 99%
“…In the paper by Korolev et al, 24 the life cycle of electric drives was considered, and their efficiency parameters during operational wear and failure periods were evaluated. At the same time, the life cycle of energy equipment was regarded as its technical condition during operation.…”
Section: Introductionmentioning
confidence: 99%
“…Counteraction to this cannot occur due to isolation, since the energy sector is not able to exist for a long time in isolation from other spheres and external influence [38,39]. As a response to challenges, end-to-end digital technologies and Industry 4.0 technologies are developing [40][41][42][43][44], stimulating the restructuring of the energy sector [45]. Authors have identified seven blocks of technologies, united by common functions or ways of realization: digital and IT, smart grid, renewable and Non-conventional energy sources, storage technologies, and a block of industrial production technologies [46,47].…”
Section: Introductionmentioning
confidence: 99%